Appointment, Discipline and Removal of Judges: A Comparison of the Swiss and New Zealand Judiciaries - Suter, Benjamin (Victoria University of Wellington Law Review, 2015)
This article gives an overview of the legal system of Switzerland and then compares the judiciaries of Switzerland and New Zealand. As far as Switzerland is concerned, it covers both the system of the Swiss Federation and the systems in the cantons. After analysing the powers enjoyed by the judiciary via the legislature, the article examines the appointment of judges in detail. The author explains how, in Switzerland, openly political and other considerations are weighed in the course of electing judges and how the appointment of lay judges is balanced with an active role of law clerks. In contrast, New Zealand has a proud tradition of apolitical judicial appointments that are made solely based on merit. The author criticises that Swiss judges are elected for a term of office, whereas New Zealand judges enjoy the security of tenure and thus, a greater judicial independence. Lastly, the article covers the removal and discipline of judges, where the author, while he commends the recent reform in New Zealand, he advocates for a system where the ultimate decision is given to an independent judicial body rather than a parliament.